Prediksi Harga Saham pada Portofolio Investor dengan Analisis Time Series Harga Saham menggunakan ANN - Wibiksana, Hendra (Bulletin of Computer Science Research, 2023)
The Indonesian Stock Exchange (BEI) is a place for stock market trading in Indonesia. In general, this is represented by the Composite Stock Price Index (IHSG) value. IHSG itself is the combined value of all shares listed on the Stock Exchange. It doesn't matter whether the shares traded that day are up, down, flat (no change in value), not traded, or even suspended (prohibited from making transactions within a certain period of time). The stock data source used is the closing price of BNI, BCA and Mandiri shares for 15 years from 2008-2022 from the Indonesian Stock Exchange (via the Yahoo Finance site). Each stock data is trained and tested, to see how accurate it is using this method. The stock prices predicted by ANN are combined into a portfolio, this portfolio will show an increase or decrease. At the end of the process, the rate of change in stock prices from predicted losses to predicted profitable stock prices is calculated. The daily data accuracy of BNI, BCA and Mandiri is 97.6927%, 97.9754% and 97.6275% respectively. Weekly data accuracy is slightly smaller than daily accuracy. The accuracy of weekly data for BNI, BCA and Mandiri is 95.7673%, 97.1222% and 96.5592% respectively. Monthly data accuracy is slightly smaller than weekly accuracy. The accuracy of BNI, BCA and Mandiri monthly data is 90.4161%, 94.781% and 93.0619% respectively. If an investor focuses all his funds on buying just one share, he will get 3 times the portfolio profit from before. If the profit on BNI shares is 46.12%, then in terms of portfolio, the investor gets a profit of 46.12% x 3 = 138.36%. Compare this with the profit levels of the 3 banks, which if added up, the value becomes as follows: 46.12+54.42+56.01 = 156.55%. So there is an additional profit from the portfolio of 156.55% - 138.36% = 18.19%.